Asymmetric information and roll-over risk - Philipp König; David Pothier (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
How do banks choose their debt maturity structure when credit markets are subject to information frictions? This paper proposes a model of equilibrium maturity choice with asymmetric information and endogenous roll-over risk. We show that in the presence of public signals about firms' creditworthiness (credit ratings), firms choose to expose themselves to positive roll-over risk in order to minimize price distortions. Short-term financing is socially desirable when banks' capacity to repay short-term creditors depends on their credit rating, as it helps mitigate the underlying adverse selection problem. Notwithstanding these social benefits, the equilibrium maturity structure always exhibits inefficient short-termism. If banks receiving a credit downgrade face sufficiently high roll-over risk, the equilibrium maturity structure approaches the constrained efficient allocation.
Keywords: G10; G20; G30; G32; 330; Debt Maturity; Rollover Risk; Asymmetric Information; Global Games